2003
DOI: 10.1034/j.1399-302x.2003.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in growth and polyglucose synthesis in response to fructose metabolism byFusobacterium nucleatumgrown in continuous culture

Abstract: Fusobacterium nucleatum, grown in a chemically defined medium at micro(rel) = 0.5, produced greater cell yields and undetectable levels of intracellular polyglucose (IP) when fructose was substituted for glucose. The utilisation and metabolism of fructose by growing cells was studied and the effect of the energy-yielding amino acids, glutamate, serine, histidine and lysine on cell yield, IP synthesis and acidic end-products was investigated. When F. nucleatum was grown on elevated amino acid levels, IP was syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It has been reported that in resting (non-growing) cells the fermentation of glutamate and lysine occurs preferentially and the energy produced is used for the active transport of glucose, which is stored as intracellular polysaccharide (IP) (Robrish et al, 1987;Robrish & Thompson, 1990). Our earlier studies on F. nucleatum growing in continuous culture showed that during glutamate fermentation, growth at pH 7.8 produced maximum levels of IP (Zilm et al, 2003). It has been reported that high levels of glutamate are present in the inflamed periodontium (Singer & Kleinberg, 1983), and fructose diphosphate has been previously described as a branch point in determining the fate of glucose into energy (ATP) or synthesis of IP (Robrish & Thompson, 1990).…”
Section: Proteins Regulated By Alkaline Phmentioning
confidence: 99%
“…It has been reported that in resting (non-growing) cells the fermentation of glutamate and lysine occurs preferentially and the energy produced is used for the active transport of glucose, which is stored as intracellular polysaccharide (IP) (Robrish et al, 1987;Robrish & Thompson, 1990). Our earlier studies on F. nucleatum growing in continuous culture showed that during glutamate fermentation, growth at pH 7.8 produced maximum levels of IP (Zilm et al, 2003). It has been reported that high levels of glutamate are present in the inflamed periodontium (Singer & Kleinberg, 1983), and fructose diphosphate has been previously described as a branch point in determining the fate of glucose into energy (ATP) or synthesis of IP (Robrish & Thompson, 1990).…”
Section: Proteins Regulated By Alkaline Phmentioning
confidence: 99%
“…However, a three-fold increase in glucose utilisation and IP was observed (Table 2, Figure 3). It is possible that the observed increase in glucose storage may play an important role in the organism’s survival during periods of nutrient limitation when exposed to pH 8.2 [43,49,50]. Although the expression of glycolytic enzymes was not significantly altered, an increase in lactate dehydrogenase (LDH) (EC 1.1.2.8) and a three-fold increase in lactate production was observed, indicating a metabolic shift at pH 8.2 towards ATP generation via anaerobic glycolysis (Embden-Meyerhof-Parnas pathway) (Tables 1 and 2, Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Fusobacterium can produce secondary and tertiary bile acids, which affect systemic glucose metabolism and energy expenditure, thereby influencing skeletal muscle metabolism [27].…”
Section: Effect Of Probiotics On Skeletal Muscle Metabolism and Relat...mentioning
confidence: 99%